Clinical utility of transperineal template-guided mapping prostate biopsy in a selection of patients under active surveillance and confirmation of patients with negative biopsy for prostate cancer - Koo, Michael Jakun; Lee, Byunghun; Song, Wan; Kang, Minyong; Sung, Hyun Hwan; Jeong, Byong Chang; Seo, Seong Il; Jeon, Seong Soo; Lee, Chung Un; Jeon, Hwang Gyun (Frontiers in Oncology, 2025)
PurposeWe investigated the change to definitive treatment in patients under active surveillance (AS) and cancer diagnosis in non-cancerous patients for prostate cancer after confirmatory transperineal template-guided mapping biopsy (TTMB).Materials and methodsA total of 336 patients who underwent TTMB between March 2017 and March 2023 were retrospectively reviewed, with 134 AS patients and 202 non-cancerous patients. All patients were routinely followed up via prostate-specific antigen (PSA) and multiparametric magnetic resonance imaging (mpMRI), and follow-up biopsy was performed when deemed clinically appropriate. Treatment changes in the AS and cancer detection in the non-cancerous group were analyzed. Descriptive statistics were used to analyze the retrospective data, and the Kaplan–Meier analysis was performed to indicate conversion to radical treatment in the AS group, as well as cancer detection in the previously benign non-cancerous group.ResultsOne hundred thirty-four patients under the AS protocol were analyzed, of whom 110 (82.1%) maintained AS for 33 months. Nine patients (6.7%) had significant findings in mpMRI [Prostate Imaging–Reporting and Data System (PI-RADS) ≥3] and received radical treatment following target biopsy via transrectal ultrasonography. A total of 115 patients (83.3%) with insignificant findings in mpMRI (PI-RADS 1 or 2 lesions) were followed up via transrectal ultrasound-guided prostate biopsy (17.4%, N = 20), repeat TTMB (6.1%, N = 7), or no additional biopsy (76.5%, N = 88), and from each group, five (25.0%), two (28.5%), and eight (9.1%) patients converted to radical treatment. In the non-cancerous group, five patients (2.5%) were diagnosed with prostate cancer, with PI-RADS ≥ 3 findings via mpMRI, and were confirmed by target biopsy during a mean follow-up period of 25 months, subsequently receiving radical treatment.ConclusionsTTMB is effective in selecting patients for AS treatment and confirming benign patients and can be used as an effective follow-up modality.